Overweight or Obese Individuals at Eighteen Years of Age Develop Pancreatic Adenocarcinoma at a Significantly Earlier Age - David T. Chao; Nilesh H. Shah; Herbert J. Zeh; Aatur D. Singhi; Nathan Bahary; Kevin M. McGrath; Kenneth E. Fasanella; Amer H. Zureikat; David C. Whitcomb; Randall E. Brand (Gastroenterology Research and Practice)
Background. Adolescent obesity is a national epidemic that recently has been shown to increase risk for pancreatic adenocarcinoma (PC) and is associated with an earlier age of PC onset. We hypothesized that PC patients who are overweight or obese at age 18 would have an earlier age of PC onset. Methods. Retrospective review of 531 patients in our PC registry was completed. Self-reported weight at age 18 and maximum lifetime weight were used to calculate body mass index (BMI) at age 18 (BMI-18) and maximum lifetime BMI. Results. Complete BMI and baseline covariate data was available in 319 PC patients. Mean age (in years) of PC diagnosis for patients whose BMI-18 was overweight (64.0) or obese (59.9) was significantly different when compared to patients with a normal BMI-18 (66.7). No significant difference was observed in the mean age of PC diagnosis in those patients who maintained a normal BMI-18 when compared to those patients who subsequently became overweight or obese (67.0 versus 66.6; p=0.65). Conclusions. An elevated BMI at age 18 is associated with an earlier age of PC onset and should be factored into determining the optimal age of beginning screening for patients at high risk for PC.